2019
DOI: 10.3892/etm.2019.7655
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of osteoarticular tuberculosis via metagenomic next‑generation sequencing: A case report

Abstract: Osteoarticular tuberculosis (OAT) may cause severe complications and disability. Due to its indolent nature, OAT is difficult to diagnose in the early stages. Diagnosis by conventional culture is time-consuming and insensitive, and polymerase chain reaction-based molecular diagnostic methods are incapable of excluding co-infections. Metagenomic next-generation sequencing (mNGS) may identify a broad spectrum of microorganisms, including Mycobacterium, bacteria and fungi, in clinical specimens. Therefore, the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…It is anticipated that within the next decade, detection and characterization of pathogens via metagenomics-based workflows will be routine in diagnostic and public health laboratories (Forbes et al, 2017). However, published reports describing the usefulness of mNGS in patients with TB are limited to individual patients or small case series (Zhou et al, 2019;Sinkov et al, 2019;Wang et al, 2019;Ai et al, 2018;Huang et al, 2019). Little is known about the sensitivity and clinical utility of mNGS for the diagnosis of pulmonary TB compared with conventional tests.…”
Section: Introductionmentioning
confidence: 99%
“…It is anticipated that within the next decade, detection and characterization of pathogens via metagenomics-based workflows will be routine in diagnostic and public health laboratories (Forbes et al, 2017). However, published reports describing the usefulness of mNGS in patients with TB are limited to individual patients or small case series (Zhou et al, 2019;Sinkov et al, 2019;Wang et al, 2019;Ai et al, 2018;Huang et al, 2019). Little is known about the sensitivity and clinical utility of mNGS for the diagnosis of pulmonary TB compared with conventional tests.…”
Section: Introductionmentioning
confidence: 99%
“…Just like the biopsies in our case, histopathological examination sometimes only shows granulomas without typical caseous necrosis, which is non-specific for the diagnosis of TB. PCR is a valuable diagnostic technique, but it always requires presupposing specific pathogens, which sometimes cannot detect rare pathogens and mixed infections ( 21 ). Additionally, Xpert MTB/RIF, a new automated molecular test, has been endorsed by WHO for the initial detection of TB and rifampicin resistance ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a case of knee joint infection, Huang et al . identified the pathogen as M. tuberculosis complex using metagenomic next‐generation sequencing 61 . Using this technique, one case in our study was diagnosed as a multi‐bacterial mixed infection that included M. tuberculosis .…”
Section: Discussionmentioning
confidence: 99%
“…Second-generation sequencing is a relatively new technique for identifying pathogens, and is more advantageous for multi-bacterial infections. In a case of knee joint infection, Huang et al identified the pathogen as M. tuberculosis complex using metagenomic next-generation sequencing 61 . Using this technique, one case in our study was diagnosed as a multi-bacterial mixed infection that included M. tuberculosis.…”
Section: Diagnosis Of Joint Tuberculosis and Tbpjimentioning
confidence: 99%